Making Mathematics Come Alive: The Effect of Implementing Recommended Teaching Strategies in the College Classroom. - Angela Humphrey Brown; Anna P. Uhde (Adult Education Research Conference, 2000)
This study examines the experiences of adult students during the implementation of recommended adult education practices in a mathematics methods course. The purpose of the study was to discover what effect utilizing adult education teaching strategies had on graduate students who perceived themselves as uncomfortable or inadequate in mathematics.